A Theoretical Reflection on the Past, Present, and Future of Employee-Organization Relationship: A Systematic Literature Review - Rezazadeh, Fatemeh; Seyyed-Naghavi, Mir Ali; Rezazadeh, Sima (UI Scholars Hub, 2023)
Considering the changes in the social and economic environment in the past two decades and their ongoing status in the new century, it is unanimously believed that the nature of employee-organization relationship (EOR) has changed significantly. EOR, as a research field, has increasingly been recognized as a locus of research on organizational behavior, human resource management, and employment relationships. There is a research demand to integrate the academic literature to reach a better understanding of EOR. Adopting the methodology of systematic literature review proposed by Centobelli et al. (2017), the present research provides a comprehensive analysis of eighty pieces of EOR research published from 1990 to 2020. The information on authors, publication year, journals, types of article, research foci, methodologies, theoretical frameworks, and recommendations for future research based on research gaps is tabulated and presented. Three theoretical gaps are identified in the current EOR research: a lack of research on the organizational context, on the integration of micro- and macro-level EOR, and on the multidimensional analysis of individual behavior, organizational context, and employment relationships. Theoretical gaps, results, discussion, and the conceptual framework proposed for future studies are also presented. Finally, strengths and limitations of the study are discussed.